OTONOMI DAERAH DAN PENGARUHNYA TERHADAP KEBIJAKAN DAERAH BERNUASA SYARIAH DI KOTA PADANG - Heru Permana Putra; Desi Syafriani (Islam Transformatif : Journal of Islamic Studies, 2019)
Sharia-based policies can be understood as tangible manifestations in increasing regional participation in the development of religious life and assisting government work programs. The Mayor of Padang gave rise to sharia-based policies because seeing the condition of the students in Padang many did not care about the rules set in religion and many had violated the rules and norms of religion prevailing so far in the Minangkabau culture in general and the City of Padang in particular, as well as many students who are not good at reading the Koran and other religious rituals such as prayer, remembrance and so on. For the political elite, the ABS-SBK space is not only a cultural construction but also a political space. They make the cultural jargon as a policy orientation through the emergence of regional regulations, so that ABS-SBK becomes something formal-legalistic. From mapping the formulation of policy models, sharia-based policies use a more problem-oriented policy formulation process.